2014
DOI: 10.1167/iovs.13-11708
|View full text |Cite
|
Sign up to set email alerts
|

Egr-1mRNA Expression Is a Marker for the Direction of Mammalian Ocular Growth

Abstract: Egr-1 mRNA levels in a mammalian retina show a bi-directional persistent response to opposing ocular growth stimuli. This suggests retinal Egr-1 might act as a signal for the direction of ocular growth in different species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 51 publications
(84 reference statements)
0
41
0
Order By: Relevance
“…2a, b). The previously reported myopia-related genes (Ashby et al, 2014, Hawthorne and Young, 2013, Ma et al, 2014, Mathis et al, 2014, McGlinn et al, 2007, Ritchey et al, 2012, Wisard et al, 2011, Yoshikawa et al, 2014) such as Bmp2, Ednrb, Fgf2, Igf1, Il18, Irbp, Lumican, Sfrp1, Tgfb1, Vegfa, Vip, and Wnt2b were not found in the PC1 group in vivo , which indicates that they responded less to violet light. In the PC1 group, only one myopia protective gene (Pardue et al, 2013), EGR1 (ZENK, zif268), was found among the previously reported myopia related genes (Fig.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…2a, b). The previously reported myopia-related genes (Ashby et al, 2014, Hawthorne and Young, 2013, Ma et al, 2014, Mathis et al, 2014, McGlinn et al, 2007, Ritchey et al, 2012, Wisard et al, 2011, Yoshikawa et al, 2014) such as Bmp2, Ednrb, Fgf2, Igf1, Il18, Irbp, Lumican, Sfrp1, Tgfb1, Vegfa, Vip, and Wnt2b were not found in the PC1 group in vivo , which indicates that they responded less to violet light. In the PC1 group, only one myopia protective gene (Pardue et al, 2013), EGR1 (ZENK, zif268), was found among the previously reported myopia related genes (Fig.…”
Section: Resultsmentioning
confidence: 74%
“…EGR1 was first found to be involved in the suppression of elongation in the chick eye (Fischer et al, 1999), and the eye elongated when EGR1 was knocked down in mouse (Schippert et al, 2007), suggesting this gene is one of the most important genes related to myopia progression. Ashby et al (2014) reported that Egr-1 mRNA levels were elevated to almost 2x the control after 3 days recovering from −5 D lens removal in a guinea pig model. In the current study, EGR1 mRNA levels in VL+ group were elevated to almost 2x the VL– group in both control and covered eyes (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Further evidence of the protective effects of bright light have been shown in a number of experiments with animal models. Using chickens (Ashby et al, 2009; Ashby and Schaeffel, 2010; Ashby et al, 2014; Backhouse et al, 2013; Lan et al, 2014), primates (Smith et al, 2012), and tree shrews (Norton and Siegwart, 2013), bright light has been reported to decrease the myopic shift induced by FD or lens defocus (Ashby and Schaeffel, 2010). These protective effects have been attributed to increased retinal DA levels and DA receptor activation as the DA D 2 -like receptor antagonist, spiperone blocks the protective effects of bright light (Ashby and Schaeffel, 2010).…”
Section: Effects Of Altered Da Levels On Myopic Eye Growthmentioning
confidence: 99%
“…We chose EGR1 as a candidate gene for association analysis of myopia, based on its functionality evidence: (1) Animal model studies of induced myopia and gene knock-out have all demonstrated the important role of EGR1 in myopia (Schippert et al, 2007); (2) EGR1 is a critical protein for eye growth and myopisation (Fischer et al, 1999;Ashby et al, 2014). The SNP rs11743810 selected here is itself the tSNP covering the EGR1 gene region's LD plot with an r 2 of 1.000 00 and an estimated power for association test of 0.997 83 (Table 4), suggesting the high efficiency of the association analysis.…”
Section: Egr1 Gene Resultsmentioning
confidence: 99%
“…Fischer et al (1999) also found a significant association of the EGR1 expression level in the retina with eyeball growth in the animal model. Moreover, a recent myopia animal study indicated that EGR1 might play a role in signaling eye growth bidirectionally (Ashby et al, 2014). However, Li et al (2008) screened mutations in the EGR1 gene region in a small group of unrelated high myopia individuals (n=96), but found no causal variations in their work.…”
mentioning
confidence: 99%